Enzyme-Like Properties of Gold Clusters for Biomedical Application - Zhang, Yunguang; Li, Shuo; Liu, Haile; Long, Wei; Zhang, Xiao-Dong (Frontiers in Chemistry, 2020)
In recent years, the rapid development of nanoscience and technology has provided a new opportunity for the development and preparation of new inorganic enzymes. Nanozyme is a new generation of artificial mimetic enzyme, which like natural enzymes, can efficiently catalyze the substrate of enzyme under mild conditions, exhibiting catalytic efficiency and enzymatic reaction kinetics similar to natural enzymes. However, nanozymes exist better stability than native enzymes, it can still maintain 85 % catalytic activity in strong acid and alkali (pH 2~10) or large temperature range (4°C~90°C). This provides conditions for designing complex catalytic systems. In this review, we discussed the enzymatic attributes and biomedical applications of gold nanoclusters, including peroxidase-like, catalase-like, detection of heavy metal ions, and therapy of brain and cancer etc. This review can help us understand the current research status nanozymes.